Transmucosal Fine Needle Aspiration of Oral and Pharyngeal Lesions. (15th June 2011) - Deng, Fang-Ming; Hsu, Jack; Khurana, Kamal K.
Abstract : Fine Needle aspiration (FNA) studies of oropharyngeal lesions are few and limited. We retrospectively reviewed cytologic diagnosis and cytohistologic correlation of 28 cases of FNAs of oropharyngeal lesions. Cytologically, 11 cases were diagnosed as malignant/suspicious and 17 cases as benign. Ten of these cases diagnosed as malignant/suspicious correlated with the subsequent histological diagnosis or were compatible with previous histological diagnoses. One case categorized as suspicious for malignancy revealed pleomorphic adenoma with extensive squamous metaplasia. Of the 17 cases diagnosed as benign by cytology, 11 correlated with the subsequent histological diagnosis. The remaining 6 cytologically benign cases were considered clinically benign, and there was no histological followup. Clinical followup on these 6 patients did not reveal any evidence of disease. The sensitivity, specificity, and accuracy of malignant diagnosis were 100%, 95%, and 97%. FNA biopsy may be used as the first line of investigation in evaluation of oropharyngeal lesions.